Medicinal and aromatic plants of the world. Volume 3 - Neffati, M.; Najjaa, Hanen; Máthé, Á (Springer, 2017)
This volume in the series is devoted to Africa, a continent that possesses a vast treasure of medicinal plants and has produced some exclusive materials for the world market. This book is expected to strengthen the medicinal plant sector in African countries by providing comprehensive information on medicinal and aromatic plants available to policy-makers and entrepreneurs to frame effective policies and create an environment conducive to the growth of the plant-based medicine industry, bringing economic benefit to African nations from the rising world demand for medicinal plants. It will help health organizations to improve the health of their people by using their own resources and a less expensive system of medicine, which is accepted by African society. It could also lead scientific communities to increase R & D activities in the field.
Includes index.
Keywords: Medicinal plants -- Africa.; Aromatic plants -- Africa.; Africa.; elektronické knihy; electronic books